The Influence of Mathematical Test Anxiety and Self-Efficacy on Students’ Performance - Arnold Dela Cruz; Melodina Dela Cruz (Universal Journal of Educational Research)
The purpose of this study was to investigate the relationships between the students’ self-efficacy, test anxiety and performance on Mathematics of Saint Joseph College, Junior High School Department for SY 2019-2020. The respondents of the study were randomly chosen junior high school students. A descriptive correlational method of research was used. The data gathered were statistically treated using the Excel and IBM SPSS programs, which summarize the percentage scores, weighted means, correlation coefficients, independent t-test values, and corresponding p-values of relevant statistical tools. Findings indicated that, at average, the students were not confident on their mathematical self-efficacy, moderately anxious on their mathematical test anxiety and satisfactory on their mathematical performance. More findings showed that the following variables have significant relationships: mathematical anxiety and mathematical self–efficacy; mathematical self-efficacy and mathematical performance; and mathematical test anxiety and mathematical performance. The higher the self-efficacy level, the lower the degree of test-anxiety; the higher the self-efficacy, the better the mathematics performance; and the lower the test anxiety, the better the performance. The study recommends regular conduct of diagnostic tests on mathematical self-efficacy and test anxiety and design programs to address the enhancement of learners’ mathematical self-efficacy and reduce their mathematical test anxiety. The researcher recommends Mathematics Learning Development Program (MLDP) as the output of the study.